Multidisciplinary care for patients with epidermolysis bullosa from birth to adolescence: experience of one Italian reference center - Chiara Retrosi; Andrea Diociaiuti; Cristiana De Ranieri; Marialuisa Corbeddu; Claudia Carnevale; Simona Giancristoforo; Maria Rosaria Marchili; Guglielmo Salvatori; Marta Luisa Ciofi degli Atti; May El Hachem; Massimiliano Raponi (BMC, 2022)
Abstract Background Epidermolysis bullosa (EB) is a disabling and chronic genodermatosis characterized by mucocutaneous fragility with blister formation after minimal trauma. Severity ranges between very mild forms to extremely severe or lethal subtypes. Depending on disease subtypes, blisters may be localized also in larynx, bladder, esophagus, and most frequent disease complications are malnutrition, chronic anemia, osteoporosis, limb contracture and early development of squamous cell carcinomas. EB is classified into four major groups: EB simplex (EBS), junctional EB (JEB), dystrophic EB (DEB) and Kindler EB (KEB). No specific treatment is available; however, a multidisciplinary management is mandatory in order to treat the lesions, to prevent complication, and to give a psychological support to the patient and family members. Objective To report the experience on a therapeutic education plan of an Italian reference center for epidermolysis bullosa in the last 30 years. Methods In our study we included all patients with EB from 1990 to the present, dividing them into three age groups (< 5 years, > 5-12 years and > 12-18 years). The therapeutic plan involved all multidisciplinary team members, since born until adolescence. The multidisciplinary team has been progressively established; the dermatologists act as patient case manager, in collaboration with the pediatrician, endocrinologist, dietician, dentist, plastic surgeon, digestive surgeon, geneticist, psychologist and a dedicated nurse. Other dedicated specialists are involved upon patient needs. Results Two hundred fifteen patients have been recruited and followed in our hospital since 1990. One hundred forty patients (65%) are on follow-up, 27 patients (13%) died and only 11 (5%) were lost to follow-up. Our patients manifested the specific complications related to their EB subtype in keeping with the data reported in the literature. Eighteen (8%) patients affected with JEB severe died within the first year of life, 9 patients (5%) died for squamous cell carcinoma in adulthood and were affected with recessive DEB; only 1 patient died for squamous cell carcinoma at the age of 16. Conclusions An adequate management of EB patients require a multidisciplinary approach with an educational plan to guarantee an appropriate treatment and to support and accompany patients and their families since birth along life. The dynamic educational plan adopted in our hospital showed good clinical and psychological outcome in our population, allowing adherence to treatment, reducing the frequency of complications and improving life expectancy and quality of life.